1991
DOI: 10.1159/000282243
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Modulation of the Micturition Reflex at the Level of the Pontine Micturition Center

Abstract: In precollicular decerebrate cats and dogs the intravenous administration of naloxone reduced urinary bladder capacity. Successive cystometrograms revealed that naloxone in doses of 10–100 µg/kg i. v. reduced the volume necessary to evoke micturition by 21–67% (mean 48%) in cats and 15–81% (mean 43%) in dogs, respectively. Microinjection of fentanyl (0.4–10 nM) into the pontine micturition center (PMC) increased the bladder capacity by 4–46% (mean 18%) in cats. Naloxone injected into the same site reversed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 11 publications
2
30
2
Order By: Relevance
“…The present results demonstrating an inhibitory function of supraspinal opioid receptors are consistent with results of studies in decerebrate cats and dogs showing that injections of fentanyl, a -opioid receptor agonist, into the PMC increases bladder capacity during saline CMGs, an effect reversed by injection of naloxone into the PMC (17). This experiment establishes the presence of opioid-inhibitory receptors in the PMC.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present results demonstrating an inhibitory function of supraspinal opioid receptors are consistent with results of studies in decerebrate cats and dogs showing that injections of fentanyl, a -opioid receptor agonist, into the PMC increases bladder capacity during saline CMGs, an effect reversed by injection of naloxone into the PMC (17). This experiment establishes the presence of opioid-inhibitory receptors in the PMC.…”
Section: Discussionsupporting
confidence: 92%
“…This selectivity suggests that neuromodulation targets the afferent limb of the micturition reflex or the supraspinal switching mechanism in the PAG-PMC circuitry but does not alter the efferent (motor) limb of the circuit. Local injections of neurotransmitters or their antagonists into the PMC of decerebrate cats can elicit similar selective changes in bladder capacity without altering the amplitude of reflex bladder contractions (12,17), providing further support for the proposal that the PAG-PMC circuitry is a likely site of action of TNS.…”
Section: Discussionmentioning
confidence: 62%
“…Naloxone administered intracerebroventricularly also reverses the effects of systemically administered morphine. Naloxone administered alone intracerebroventricularly or injected directly into the PMC facilitates the micturition reflex, indicating that micturition is tonically inhibited by a supraspinal opioid mechanism (264,478). Both μ and δ opioid receptors mediate inhibitory effects that are blocked by naloxone (264,398).…”
Section: Pontine Micturition Center and Supraspinal Pathwaysmentioning
confidence: 99%
“…The tonic enkephalinergic inhibition of the micturition reflex is believed to be mediated at several possible levels, including the peripheral bladder ganglia, sacral spinal cord, or brainstem (Noto et al, 1991). Studies using several types of MOR drugs have shown that the MOR modulation of bladder motility is exerted both at supraspinal and spinal sites in various species.…”
Section: A New Drug Candidate For Overactive Bladdermentioning
confidence: 99%
“…Opioids have been well known to exert an inhibitory effect on the micturition reflex at various CNS sites, including the pontine micturition center (Noto et al, 1991), sacral parasympathetic nucleus (de Groat et al, 1983), and urethral sphincter motor nucleus in the spinal cord (Thor et al, 1989). Thus, opioid receptors are believed to be potential molecular targets for drugs acting on the CNS for OAB treatment.…”
Section: Introductionmentioning
confidence: 99%